Morfoanatomia e micromorfologia comparada das folhas de espécies de Psidium L. (Myrtaceae) do Cerrado Goiano - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
The Cerrado biome has the largest diversity among the world's savannas, which is the predominant biome in the state of Goiás. The anthropization and advances in agricultural and animal husbandry frontiers have been causing strong impact on the Cerrado. One serious consequence has been the extinction of native plant species even before they are described. The Myrtaceae family stands out among the 12,000 plant species that have been cataloged in the Cerrado biome. This family represents a great economic potential because of its medicinal properties, such as diuretic, anti-inflammatory, anti-rheumatic, antioxidant, antimicrobial, anti-proliferative on human tumor cells, among others; used in food and ornamental, as well as its ecological importance. The most representative genus of this family are: Eugenia (subtribe Eugeniinae), Myrcia (subtribe Myrciinae), Psidium and Campomanesia (subtribe Myrtinae). In the Cerrado, the Psidium genus stands out, represented by guava and araçazeiros. Due to the large phenotypic plasticity of the Psidium species, consequence from several environmental pressures to which they are subjected, research on architecture aspects, anatomy and leaf micromorphology can be critical in solving systematic problems and taxonomy of this genus. The objective of this study was to assess interspecific variations of four species of Psidium collected in the Cerrado, based on morphoanatomical and micromorphological characters of its leaves. Thus, leaves samples of Psidium firmum O. Berg, Psidium myrsinites DC., Psidium laruotteanum Cambess., and Psidium guineense Sw. were collected from Universidade Estadual de Goiás (Trilha do Tatu), Base Aérea de Anápolis and Parque Estadual da Serra de Caldas Novas. In addition, two species were studied from related genus, one belonging to Campomanesia, and another, Eugenia. The samples were submitted to classical techniques for analysis in optical microscopy and scanning electron, in addition to morphological and leaf venation studies. Multivariate statistics analysis were used, as the principal component analysis (PCA) and unweighted pair group method analysis (UPGMA), the distance of Jaccard and principal coordinate analysis (PCoA), to correlate the main characters of Psidium and the related species, in order to better understand their patterns of variation. 71 morphoanatomical and micromorphological characters were described, 30 were identified as significant by the PCA, and four axes of the principal components were identified, explaining the greater variation of similarity between the species. P. laruotteanum has the smallest distance from the P. myrsinites for presenting large number of coincidences in the anatomical and micromorphological characters. 13 Campomanesia adamantium was closer to Psidium for this study, holding almost the same characters; this similarity can be explained by integrating the same subtribe. A greater distance between P. firmum and P. guineense was confirmed, because of the distinctive characteristics within the group of the subtribe (Myrtinae). Eugenia punicifolia was considered the most distinctive, due to its greater distance between the six species studied, dissimilarity explained by presenting a lower amount of shared characters, which justifies its position in different subtribe (Eugeniinae). The morphoanatomical and micromorphological results of Psidium leaves presented in this study may provide important information for the characterization of their species, taxonomic and systematic studies.
Keywords: Araçá; Morfoanatomia; Taxonomia; Análise estatística multivariada; Morphoanatomy; Taxonomy; Multivariate statistical analysis; CIENCIAS BIOLOGICAS